The blank cheque and the cliff edge. (20th November 2019) - Fowler, Reg
Abstract: Recent English and Australian court decisions limit the scope of the operator's authority to incur and charge costs to the joint venture to costs incurred in activities approved by the operating committee. Surprisingly, JOAs do not routinely address the liability of the operator arising from unapproved activities, even though such activities are foreseeable and sometimes difficult to avoid. Losses and liabilities incurred by the operator, including harm to the interests of the non-operators in such circumstances, are left to law and are unlikely to be covered by joint venture insurance.